EKSISTENSI USAHA WAROENG MIE BANGLADES LHOKSEUMAWE DITINJAU DALAM PERSPEKTIF EKONOMI ISLAM - Muhammad Kharazi (SYARIAH: Journal of Islamic Law, 2023)
Waroeng mie is a general term in Aceh to refer to businesses that serve dishes in the form of noodles to the public and provide a place to enjoy these dishes and set certain rates for food and services. This research was conducted at Bangladeshi noodle waroeng, Lhokseumawe city. The purpose of this study is to find out what factors influence the existence of waroeng Bangladeshi noodles in Lhokseumawe city and how the business of waroeng Bangladeshi noodles in Lhokseumawe city maintains their business. This research is a descriptive research with a qualitative approach. Qualitative descriptive research is research that aims to describe events and phenomena that occur in the field and present information in a systematic, objective and concise manner using observation, interview and documentation techniques. Researchers use source triangulation to check the correctness of research data and draw conclusions. The results showed that the success of Waroeng Banglades Noodles in maintaining its business existence was the quality of its food products, especially the distinctive taste that Waroeng Banglades Noodles had. It's not only the taste that makes customers come back, but the affordable price is one of the reasons why customers buy continuously. Apart from that, the location of Waroeng Mie Bangladesh is very strategic, which is in the middle of the central market of the city of Lhokseumawe.